Neonatal screening for hypothyroidism by time - Resolved fluoroimmunoassay in Jharkhand - Prasad, Rameshwar; Verma, Amar; Verma, Anita (Indian Journal of Child Health, 2017)
Objective: To screen newborns for congenital hypothyroidism by time resolved fluoroimmunoassay (TRFIA) (TRFIA meter by Perkin Elmer). Methods: Participants were randomly selected from the Department of Paediatrics/Obstetrics and Gynaecology, Rajendra Institute of Medical Sciences and Maternity Hospitals around 20 km of Rajendra Institute of Medical Sciences, Ranchi. Blood samples were obtained by heel prick for thyroid-stimulating hormone (TSH) estimation from newborns selected from abovementioned hospitals. Samples were collected from 3rd day of life to 7th day of life on a filter paper card and analyzed by TRFIAbased method. Results: 60% of the newborns were male and 40% were female among 150 newborns selected for study. Out of them, 65.33% were term, 28% were pre-term, and 6.67% were post-term. 92% newborns had TSH level <10 mIU/L, 8% had TSH between 10 and 20 mIU/L and none had TSH value >20 mIU/L. Conclusion: The prevalence of borderline TSH assay was 80/1000 newborns, which is significant. Screening studies for such conditions need larger sample size, stronger logistics to cover a larger area.